PIRIBEDIL: INDICATIONS FOR ITS USE IN PSYCHIATRY AND ADDICTION MEDICINE - Yuriy Vitalievich Bykov; Roman Alexandrovich Bekker (Siberian journal of life sciences and agriculture, 2020)
Purpose. Our goal in compiling this review was to provide the reader with the comprehensive data on the receptor profile and the spectrum of pharmacological activity of piribedil (which was historically the first non-ergoline agonist D2 and D3 subtypes of dopamine receptors). Then we will discuss the putative mechanisms of its therapeutic effect, the indications for its use in psychiatry and addiction medicine (i.e., beyond its original indication in neurology, which was the treatment of Parkinson’s disease), and present to the reader the existing evidence base for its use in various mental and substance use disorders. Methodology. We have searched and reviewed the available scientific data on piribedil in search engines and databases PubMed, Google Scholar, Science Direct, Ki Database, with the use of corresponding keywords. Results. The data we have found in the process of compilation of this review indicate that, in addition to its well-known antiparkinsonian properties, piribedil may also have antidementic, pro-cognitive (nootropic), anti-amnestic, antidepressant, anxiolytic, analgesic, and vasodilating properties. The vasodilating effect of piribedil is most evident in small cerebral vessels. Piribedil also can reduce the secretion of prolactin and several other stress hormones. These properties of piribedil can determine its effectiveness as a part of the combination therapy in various forms of dementia, in mild to moderate cognitive impairment, in depressive and anxiety disorders, in attention deficit hyperactivity disorder, in somatoform and other chronic pain disorders, in depersonalization-derealization syndrome, and also as a corrector for side effects the effects of antipsychotics and as a measure to reduce negative symptoms in the treatment of schizophrenia and schizophrenia spectrum disorders. Practical implications. The results we have presented in this review deserve the widest application in psychiatry, addiction medicine and neurology.